2017
DOI: 10.1111/1758-2229.12537
|View full text |Cite
|
Sign up to set email alerts
|

The skin microbiome of the common thresher shark (Alopias vulpinus) has low taxonomic and gene function β‐diversity

Abstract: Summary The health of sharks, like all organisms, is linked to their microbiome. At the skin interface, sharks have dermal denticles that protrude above the mucus, which may affect the types of microbes that occur here. We characterized the microbiome from the skin of the common thresher shark (Alopias vulpinus) to investigate the structure and composition of the skin microbiome. On average 618 812 (80.9% ± S.D. 0.44%) reads per metagenomic library contained open reading frames; of those, between 7.6% and 12.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(142 citation statements)
references
References 104 publications
7
134
1
Order By: Relevance
“…Proteobacteria is the most common phylum reported in the skin and gill microbiomes of teleosts (see for example the review by Llewellyn et al, 2014), including the skin microbiome of seabass and seabream (Chiarello et al, 2015;Pimentel et al, 2017;Tapia-Paniagua et al, 2018). A predominance of the phylum Bacteroidetes has also been previously reported in seabass and seabream (Chiarello et al, 2015;Tapia-Paniagua et al, 2018), as well as in the skin of many other fishes, such as in the brook char , rainbow trout (Lowrey et al, 2015), channel catfish (Larsen et al, 2014), tambaqui (Sylvain et al, 2016), among others (see Doane et al, 2017;Larsen et al, 2013;Larsen et al, 2015;Legrand et al, 2018;Leonard et al, 2014). The gill microbiome of the bluefin tuna (Valdenegro-Ve g a et al, 2013), rainbow trout (Lowrey et al, 2015) and yellowtail kingfish (Legrand et al, 2018) were also found to be dominated by Bacteroidetes.…”
Section: Core Microbiome Compositionmentioning
confidence: 89%
“…Proteobacteria is the most common phylum reported in the skin and gill microbiomes of teleosts (see for example the review by Llewellyn et al, 2014), including the skin microbiome of seabass and seabream (Chiarello et al, 2015;Pimentel et al, 2017;Tapia-Paniagua et al, 2018). A predominance of the phylum Bacteroidetes has also been previously reported in seabass and seabream (Chiarello et al, 2015;Tapia-Paniagua et al, 2018), as well as in the skin of many other fishes, such as in the brook char , rainbow trout (Lowrey et al, 2015), channel catfish (Larsen et al, 2014), tambaqui (Sylvain et al, 2016), among others (see Doane et al, 2017;Larsen et al, 2013;Larsen et al, 2015;Legrand et al, 2018;Leonard et al, 2014). The gill microbiome of the bluefin tuna (Valdenegro-Ve g a et al, 2013), rainbow trout (Lowrey et al, 2015) and yellowtail kingfish (Legrand et al, 2018) were also found to be dominated by Bacteroidetes.…”
Section: Core Microbiome Compositionmentioning
confidence: 89%
“…It may be possible that bacteria found on whale skin also occur within the respiratory tract or epithelial cells. Tenacibaculum has been associated with the microbiome of other marine species such as southern bluefin tuna (Thunnus maccoyii castelnau) (Valdenegro-Vega et al, 2013), while Psychrobacter is part of the thresher shark and rainbow trout skin microbiome (Lowrey et al, 2015;Doane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial community of black-tip reef shark skin investigated in the present study was comprised of a combination of several bacterial genera previously identified to be characteristic of shark skin [27], as well as bacterial taxa common in a range of marine organisms and environments [40][41][42][43]. Bacteria previously reported characteristic of the thresher shark (Alopias vulpinus) skin microbiome, but absent in corresponding seawater samples were Erythrobacter, Idiomarina, Marinobacter, and Pseudoalteromonas [27]. Shotgun sequencing suggested these bacteria harbor potentially important functions, including the synthesis of photosynthate (Erythrobacter), heavy metal detoxification (Idiomarina), and lipopolysaccharide degradation (Marinobacter), the latter of which may mediate and reduce host inflammatory responses [27,44].…”
Section: Bacterial Community Composition Of Black-tip Reef Shark Skinmentioning
confidence: 99%
“…Skin acts as a physical barrier to the surrounding environment, protecting against invasion by foreign substances and pathogens [26,30]. Skin microbiomes are shaped in part by properties, such as topographical location, endogenous host factors, and exogenous environmental factors [27,28,58]. Skin insults, including injury, lesions, inflammation, infection, or disease, are commonly associated with microbiome shifts [31][32][33]35].…”
Section: Conserved Bacterial Communities On Healthy and Insulted Skinmentioning
confidence: 99%